Design, Development, and Performance Analysis of an Intelligent IoT-Based Home Automation System - Rajesh Kumar; Navnit Gupta (International Journal of Advanced Control and System Engineering, 2026)
Without a doubt, the incorporation of Internet of Things (IoT) technology into what used to be traditional homes has turned them into smart houses. Appliances are controlled and monitored in the distance. With a security of 99.9% it is unproblematic to break in these terminals and your energy synchronously may go down two points any time fifty times." "Home automation systems allow automatic control of electrical appliances, environmental conditions and security mechanisms. Consequently occupants living in such intelligent spaces can enjoy the benefits of greater safety, comfort and energy efficiency. In this research paper, we present the design, development and performance evaluation of an intelligent Internet-of-things home automation system based on embedded controllers, smart sensors, wireless communications technologies and cloud-based services. With the system proposed by the authors, users can remotely control household appliances, receive real-time environmental information and use a mobile phone or Web application to give instant commands. Each purpose is treated as a layer. During the course of this series we will emphasize design for modularity, scalability and reliability. Experimental results show that the system has fast response, stable communication and is energy-efficient. It is therefore suitable for today's smart homes and capable of being scaled up to meet requirements in smart communities.
Keywords: Home automation systems, Internet of Things; Smart homes, Embedded systems, Energy management systems; wireless networks